First European quality of life survey time use and worklife options over the life course - Torres, Analia; Brites, Rui.; Haas, Barbara; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
The analysis of time use over the life course is of growing relevance for several reasons. On the one hand, policymakers are interested to know about the current situation and developments in terms of the organisation of time in society and its societal and economic implications. At the same time, academic interest is growing in the life course perspective as an analytical framework which focuses on the dynamics of human life trajectories. From a life course perspective, it is possible to shed light on how people pass through the different stages of their lives, and on how they construct their life courses according to their social conditions and situational constraints. Moreover, it is possible to gain an insight into people's preferences and goals and into how their lives are shaped by institutional structures.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Living conditions -- European Union countries; Electronic books